FORMATION OF DISCIPLINE AND RESPONSIBILITY THROUGH SELF CONCEPT KARATE OF CHARACTER - Annisa Sinatrya Kusuma; Carsiwan; Asep Sumpena (SOSIOEDUKASI, 2026)
This study aims to analyze the influence of self-concept formed through the Karate of Character program on students' attitudes of discipline and responsibility. The study used a quantitative approach with an ex post facto method carried out on karate training participants at the Cisarua Karate Dojo who had participated in the program consistently. The research sample amounted to 30 students aged 12–18 years who were selected using purposive sampling techniques. Data collection was carried out through Likert scale questionnaires, observations, and documentation, then analyzed using Pearson correlation and linear regression. The results showed that self-concept had a positive and significant relationship with discipline (r = 0.782) and responsibility (r = 0.815). These findings show that strengthening self-concept through structured karate practice can contribute to shaping the character of discipline and responsibility in students.